Aplikasi Pestisida Nabati Maja - Gadung dan Metabolit Sekunder Beauveria Bassiana Bals. Untuk Mengendalikan Hama Thrips Sp. Pada Tanaman Cabai Rawit - Tarjoko Tarjoko; Mujiono Mujiono (Proceedings Series on Physical & Formal Sciences, 2021)
Pest attacks on chili plants are the main limiting factor in cultivation activities. The research aims to determine the effect of single application of botanical pesticide maja-gadung (PMG), single application of secondary metabolite Beauveria bassiana BIO (BIO B10), combined application of PMG and BIO B10 on pest populations, predator populations and plant growth and production of chili. The reesearh used a factorial Completely Randomized Block Design (RAKL) with 3 replications, so there were 9 treatment combinations (0 ml/l PMG, 4 ml/l PMG, 8 ml/l BIO B10, 0 ml/l PMG, 2 ml/l BIO B10, 4 ml/l BIO B10, 4 ml PMG+2 ml/l BIO B10, 4 ml/ml PMG+4 ml BIO B10, 8 ml/l PMG+2ml/l BIO B10, 8 ml/l PMG+4 ml/l BIO B10). The variables observed were Thrips sp population, predator population, plant height, number of leaves, and fruit weight per plant. The results showed that the single application treatment of PMG with a concentration of 4 ml/l and 8 ml/l was able to suppress the population of Thrips sp. by 21.6% and 41.4% compared to the control. The single application treatment of BIO B10 with concentrations of 2 ml/l and 4 ml/l was able to suppress the population of Thrips sp. by 66.5% and 65.5% compared to the control. The best combination application is PMG and BIO B10with a concentration of 8 ml/l + 4 ml/l which is able to suppress the population of Thrips sp. by 76.9% compared to the control. The application treatment of PMG andBIO B10 did not affect plant height, number of leaves, and fruit weight per plant.